Who fakes support for the military? Experimental evidence from Tunisia. Issue 6 (18th August 2022) - Koehler, Kevin; Grewal, Sharan; Albrecht, Holger
ABSTRACT : Surveys around the world report exceptionally high levels of support for the military. This is particularly relevant for countries in transition from authoritarian rule to democracy, where militaries can play a vital role for democratic consolidation or autocratic backsliding. Given the sensitive nature of the issue, we suspect that figures indicating strong support for the military are at least partly driven by sensitivity bias. We explore this possibility through list experiments in two nationally representative surveys in Tunisia. We find that misreporting of support for the military in Tunisia is substantial, with respondents overreporting positive attitudes by 40–50 percentage points. Moreover, misreporting is not random, but instead varies systematically by incumbency, with supporters of governing parties misreporting support for the military to a significantly higher degree than opposition supporters or non-voters. Our results suggest that public opinion researchers should be wary of using direct questions to measure support for the military.